A pilot study on exertional tasks with physiological measures designed for the assessment of military concussion - Julianna H Prim; Maria I Davila; Karen L McCulloch (Concussion)
Background: Guidelines for clinicians treating military concussion recommend exertional testing before return-to-duty, yet there is currently no standardized task or inclusion of an objective physi...